Evaluasi efektifitas pengajaran ekonomi berbasis problem based Learning di kelas XI - Aris Susanto (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research is: A. the main purpose: 1) to describe the effectiveness of model Problem Based Learning (PBL) in learning economic during the process of studing, 2) to describe the effectiveness of model Problem Based Learning (PBL) in learning economic based on studentsâ€™ responses, 3) to describe the effectiveness of model Problem Based Learning (PBL) in learning economic from the outcomes student learning. B. a common purpose is to describe the effectiveness of model Problem Based Learning (PBL) in learning economic at Class XI of social study programe 2 SMAN 2 BantulÂ This research is evaluation research. This research used the desktiptif method namely the research aimed is to explain the condition or phenomenon, while the approach that is used is the quantitative descriptive. The quantitative approach is used with consideration to obtain the knowledge thorough the economic learning based on the Problem Based Learning (PBL), so that obtained the comprehensive results.Â The results of this research are of the three learning models used to determine the effectiveness of economic learning methods Problem Based Learning (PBL) showed that: In the Input evaluation data variable student activity included in the category of Good Enough, In the process of learning by using the method of Problem Based Learning in class XI IPS 2 on economic subjects included in the category of Good, on results of student learning with Basic Competencies Describing APBN and APBD in Development included in the category of Good. so that can be concluded that the use of the learning model with the method of Problem Based Learning (PBL) shows the effective results in economic learning at class XI IPS 2 SMAN 2 Bantul 2016/2017 academic year.